Computer-based intraoral image analysis of the clinical plaque removing capacity of 3 manual toothbrushes - Staudt, Christine B.; Kinzel, Sonja; Haßfeld, Stefan; Stein, Wolfram; Staehle, Hans Jörg; Dörfer, Christof (Journal of clinical periodontology, 2001)
(I) Introducing an intraoral camera system with a special positioner to allow computer-based analysis of reproducible images on lingual tooth surfaces and (II) comparing plaque removal by three manual toothbrushes with different brushhead designs (convex, multilevel and flat trimmed) on lingual mandibular tooth surfaces.
First published: 12 January 2002
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 24.02.2021